The phosphodiesterase 10A selective inhibitor, TAK-063, induces c-Fos expression in both direct and indirect pathway medium spiny neurons and sub-regions of the medial prefrontal cortex in rats. (December 2017) - Nakatani, Atsushi; Nakamura, Sayuri; Kimura, Haruhide
Highlights: Activation of the striatum and frontal cortex was assessed by c-fos expression. TAK-063 activated similar numbers of direct and indirect pathway MSNs. TAK-063 preferentially activated sub-regions of the mPFC, such as ACC and PrL. The ACC and PrL are known to be deeply involved in cognitive function. Abstract: TAK-063, a selective phosphodiesterase 10A (PDE10A) inhibitor, produces potent antipsychotic-like and pro-cognitive effects in rodents via balanced activation of striatal direct and indirect pathway medium spiny neurons (MSNs). Brain activity modulation by TAK-063 has been characterized using pharmacological magnetic resonance imaging and electroencephalography in animals, revealing modulation of activity in the prefrontal cortex (PFC) where there is little or no PDE10A expression. To understand the specific brain regions and cells affected by TAK-063 in rats, we assessed neural activation in the striatal complex and PFC using immunofluorescence staining to measure c-Fos expression. TAK-063 at 0.3 and 3 mg/kg induced a dose-dependent increase in the number of c-Fos immunoreactive cells in the striatal complex. Furthermore, TAK-063 increased the number of MSNs expressing c-fos mRNA in both the D1 receptor-expressing direct pathway and D2 receptor-expressing indirect pathway of the striatal complex. TAK-063 (0.3 and 3 mg/kg) induced c-Fos expression in the anterior cingulate cortex (ACC) and prelimbic cortex (PrL), but not the infralimbic, dorsal peduncular, primary motor or anterior insular cortices. These findings suggest that administration of TAK-063 activates similar numbers of direct and indirect pathway MSNs, resulting in activation predominantly in medial PFC sub-regions, such as the ACC and PrL.